Pembangunan Karakter Siswa Melalui Manajemen Pelayanan Bimbingan Konseling: Membangun Pribadi Tangguh Dan Beretis - Anggraini, Yeka; Sumarsih (Manajer Pendididikan, 2024)
The aim of this research is to describe the character of students in building a resilient and ethical person. The method used in this research is comparative qualitative descriptive method. The subjects of this study were the principal, counseling guidance coordinator, and counseling guidance teacher. Data were collected using interview, observation, and documentation instruments. The analysis technique used is data reduction, data presentation, and conclusion drawing. The results showed that students showed good character at school with full ethics and became tough personalities. It can be concluded that: the formation of students’ character through the management of guidance and counseling services runs in accordance with school rules at SMP Negeri 2 Bengkulu Selatan; building a tough and ethical person with various counseling activities, namely students are involved in various school activities; factors that support and hinder are cooperation with various parties both inside and outside the school; management of counseling guidance services carried out to shape students’ character, namely by conducting social personal group counseling services with peers.